P152 CLINICAL PREDICTIVE MODEL OF LYMPH NODE METASTASIS AT RIGHT RECURRENT LARYNGEAL NERVE ZONE IN ESOPHAGEAL SQUAMOUS CELL CARCINOMA. (23rd November 2019) - Zhigang, Li; Baiwei, Li; Bin, Li; Yang, Yang
Abstract: Aim: The aim of this study is to establish a clinical predictive standard for lymph node metastasis at this location by retrospectively comparing the traditional imaging findings of RRLN lymph nodes in esophageal squamous cell carcinoma with postoperative pathology. Background: The right recurrent laryngeal nerve (RRLN) is the zone most prone to lymph node metastasis of esophageal squamous cell carcinoma. Although the survival benefit is large after surgical dissection, however, the postoperative mortality rate is significantly increased if the nerve is injured. How to selectively perform lymph node dissection at this location has always been a clinical problem that needs to be addressed. In the past, clinical evaluations mostly used lymph node short diameter ≥1cm as the diagnostic criteria for metastasis, which significantly underestimated the actual clinical situation. Methods: 308 patients with thoracic esophageal squamous cell carcinoma who underwent surgical treatment in Shanghai Chest Hospital from Jan 2018 to Dec 2018 were retrospectively analyzed. According to imaging 1mm layer thickness enhanced CT as a tool, the RRLN lymph node short diameter (ctNd) size was measured. All patients were divided into four groups: (A) CT images without RRLN lymph node, (B) CT images with RRLN lymph node was 0<ctNd<5mm, (C) CT images with RRLN lymph node was 5mm≤ctNd<10mm, (D) CT images with RRLN lymph node was ctNd≥10mm. The RRLN lymph node metastasis of each group was analyzed, and the influencing factors were analyzed to establish a predictive model. Results: Among all patients, 87.6% of the patients had lymph nodes detected in the RRLN surgical specimens. The sampling rate was 14.5% (121/832), the RRLN lymph node metastasis rate was 19.48%, and the total lymph node metastasis rate was 48.7%. RRLN lymph nodes (57.1%) (A-132, B-43, C-125, D-9) were seen in the preoperative CT scan of 176 patients. The postoperative pathological RRLN lymph node metastasis rate was 9.1%, 18.6%, 27.2% and 66.7%, respectively (P=0.01). Multivariate analysis showed that ctNd, tumor location and N stage were risk factors for RRLN lymph node metastasis (P<0.05). The risk of upper esophageal cancer metastasis was higher than middle segment esophageal cancer (28.2% vs 18.6%, P<0.05). The higher the risk of right laryngeal lymph node metastasis was detected in the later N stage (cN0-13.2%, cN1-21.5%, cN2-46.7%, P<0.05). The 6.5mm short diameter of RRLN lymph nodes on CT scan is the critical value of metastasis at this position (sensitivity 50%, specificity 83.5%), and the higher the risk of metastasis was seen in the larger the short diameter (P<0.05). Conclusion: More than 6.5mm short diameter in the CT scan image should be the clinical predictor of lymph node metastasis of the right recurrent laryngeal nerve. The higher risk of metastasis was seen in the greater short diameter. Upper esophageal cancer and multiple lymph node metastasis increase the risk of RRLN lymph node metastasis. Key words: esophageal cancer, lymph node metastasis, recurrent laryngeal nerve, computed tomography